The Implementation of Smart Energy into Transformation of the Rural Area: The Use of Public Policies for Smart Villages Development - Hlavacek, Petr; SkalnÃk, VladimÃr (International Journal of Energy Economics and Policy, 2021)
The article aims to evaluate the government policies in the Czech Republic that have an impact on energy development and energy production development in the rural areas, and to propose the areas where smart energy solutions are appropriate for rural communities. The setup of the public companies is compared with respect to current trends in the development of Smart Villages, where the smart energy solutions are being developed. The research and development conclude that the development policies will require a setup to make the decentralization of the energy sources strengthened. As well, to allow more intensive communication and negotiation with local communities. Achieving the synergy effect, while starting up the process of use of local energy resources of the location and community energy in transformation of the rural area, should be the goal. Keywords: energy policy, Smart Cities, Smart Villages JEL Classifications: Q42, Q48, R11 DOI: https://doi.org/10.32479/ijeep.11203